2022
DOI: 10.1021/acs.jafc.2c04379
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of a Collagen-Derived Protein Hydrolysate and Biostimulant Activity Assessment of Its Peptidic Components

Abstract: Protein hydrolysates (PHs) are plant biostimulants consisting of oligopeptides and free amino acids exploited in agriculture to increase crop productivity. This work aimed to fractionate a commercial collagen-derived protein hydrolysate (CDPH) according to the molecular mass of the peptides and evaluate the bioactivity of different components. First, the CDPH was dialyzed and/or filtrated and analyzed on maize, showing that smaller compounds were particularly active in stimulating lateral root growth. The CDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Nesse contexto, os bioestimuladores de colágeno surgem como uma excelente opção para tratar os sinais do envelhecimento, promovendo uma resposta inflamatória que estimula a produção de colágeno perdido. Esses bioestimuladores atuam nas camadas mais profundas do tecido, visando obter uma pele mais jovem e revitalizada (Ambrosini et al, 2022).…”
Section: Resultsunclassified
“…Nesse contexto, os bioestimuladores de colágeno surgem como uma excelente opção para tratar os sinais do envelhecimento, promovendo uma resposta inflamatória que estimula a produção de colágeno perdido. Esses bioestimuladores atuam nas camadas mais profundas do tecido, visando obter uma pele mais jovem e revitalizada (Ambrosini et al, 2022).…”
Section: Resultsunclassified
“…Using high-throughput phenotyping and metabolomics approaches, they showed the growth promotor and stress alleviator effects of those hydrolysates through the coordinated action of plant growth regulators and antioxidant compounds, such as phenolics and carotenoids. Ambrosini et al showed that the removal of free amino acids and short peptides through filtration and dialyses of a commercial collagen-derived protein hydrolysate lowered its biostimulating effect on the roots of maize plants, grown in hydroponic solution, showing that smaller compounds were particularly active in lateral root development [75].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4a shows that the emulsification stability of CHC continues to decrease with increasing concentration. This indicates that collagen surface tension increased due to macro-molecular aggregation and decreased hydrophobicity [33].…”
Section: Emulsification and Emulsion Stabilitymentioning
confidence: 96%
“…The sample also has a peaked shape in the 1340 cm −1 band, representing the CHC showing the characteristics of proline side-chain rocking vibration [2]. In addition, a C-N stretching vibration at 1409 cm −1 suggests an interaction between the amide group and the molecule of the triple helix structure [33]. No absorption band corresponding to the carboxyl functional group was found in CHC (1740-1720 cm −1 ), consistent with the lyophilized pure collagen results previously reported in the literature [19].…”
Section: Chc Amino Acid Compositionmentioning
confidence: 96%